Pengaruh Quick Ratio, Debt To Equity Ratio, Return On Asset Dan Total Asset Turnover Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Basic materials Industri Wadah dan Kemasan Tahun 2019-2023 - Muhamad Syambas; Astrid Dita Meirina Hakim (CV. ULIL ALBAB CORP, 2024)
This research aims to examine the partial effects of the quick ratio, debt to equity ratio, return on assets, and total asset turnover on company value within the basic materials sector, specifically in the container and packaging industry, listed on the Indonesia Stock Exchange for the period 2019 – 2023. The research sample comprises 14 companies within the basic materials sector of the container and packaging industry listed on the Indonesia Stock Exchange during the period 2019-2023. This study employs panel data regression statistical analysis tools, facilitated by Eviews version 12 and Microsoft Excel 2013. The findings indicate that the quick ratio has a partially negative and significant impact on company value. Conversely, the debt to equity ratio, return on assets, and total asset turnover each have no partial effect and are not significant in relation to company value.